2021
DOI: 10.3390/molecules26041026
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Molecular Characteristics of Hydrochars by 13C-NMR and Off-Line TMAH-GC/MS and Assessment of Their Potential Use as Plant Growth Promoters

Abstract: Hydrochar is a carbon-based material that can be used as soil amendment. Since the physical-chemical properties of hydrochar are mainly assigned to process parameters, we aimed at evaluating the organic fraction of different hydrochars through 13C-NMR and off-line TMAH-GC/MS. Four hydrochars produced with sugarcane bagasse, vinasse and sulfuric or phosphoric acids were analyzed to elucidate the main molecular features. Germination and initial growth of maize seedlings were assessed using hydrochar water-solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 61 publications
0
11
0
1
Order By: Relevance
“…The relative preservation of apolar compounds during the dynamics of natural organic materials such as litter, soil organic matter, compost, digestates, etc. are in fact closely correlated with the advancement of carbon stabilization and the so-called humification process [29,34]. Bioactive properties are thus triggered by depolymerized organic molecules released by the intense humification process, mainly represented by aromatic and phenolic compounds and decomposed peptide moieties [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative preservation of apolar compounds during the dynamics of natural organic materials such as litter, soil organic matter, compost, digestates, etc. are in fact closely correlated with the advancement of carbon stabilization and the so-called humification process [29,34]. Bioactive properties are thus triggered by depolymerized organic molecules released by the intense humification process, mainly represented by aromatic and phenolic compounds and decomposed peptide moieties [48].…”
Section: Discussionmentioning
confidence: 99%
“…The A/OA and HB indices are mainly used as references to determine the biochemical stability of organic matrices and correlate the structural composition with the stabilization processes of organic materials [28,29]. The Lig R ratio is a useful indicator to discriminate between NMR signals due to lignin and other phenolic compounds (lower LigR) versus the prevalent contribution of peptidic moieties (larger LigR) in the 45-60 ppm range of the NMR spectra [17,30].…”
Section: Analysis Of the Molecular Carbon Components Of Compostmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact opposite effect on seedling growth and the pyrolysis temperature was observed by Kong et al (2021). Fregolente et al (2021) created hydrochar extracts via a phosphoric acid treatment and observed elevated bioavailable lignin-derived compounds. These compounds appeared to enhance corn seedling growth.…”
Section: Introductionmentioning
confidence: 92%
“…These authors contended that the antagonistic effect on seed vitality was likely due to the presence of bio-oil, i.e., aromatic compounds, in the biochar, creating biological toxicity. Oppositely, Fregolente et al (2021) found that the benzene derivatives and phenolic compounds, i.e., both aromatic compounds, present in the biochars were responsible for stimulating the shoot and root elongation.…”
Section: Three-dimensional Excitation-emission Matrix Spectrophotomet...mentioning
confidence: 99%